2014
DOI: 10.1039/c4cc03203a
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and reaction of sub-monolayer films of an ionic liquid on Cu(111)

Abstract: The reactive interaction of the ionic liquid 1-butyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide [BMP][TFSA] with Cu(111) was investigated by scanning tunnelling microscopy (STM) and X-ray photoelectron spectroscopy (XPS) under ultrahigh vacuum (UHV) conditions. Decomposition between 300 K and 350 K is manifested by changes in the surface structure monitored with STM. XPS reveals that mainly the [TFSA] anion is decomposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
72
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(83 citation statements)
references
References 17 publications
10
72
1
Order By: Relevance
“…Many established UHV-based surface science techniques have successfully contributed to an increasingly detailed understanding not only of the IL/ vacuum interface, but also of IL bulk properties. The applied methods include X-ray photoelectron spectroscopy (XPS) [106,107,, UV photoelectron spectroscopy [138,139,165,166], inverse photoelectron spectroscopy (IPES) [165,166], X-ray absorption spectroscopy (NEXAFS) [165], soft X-ray emission spectroscopy (SXES) [166], low energy ion scattering (LEIS) [141], metastable ion spectroscopy (MIES) [138,139], time-offlight secondary mass spectroscopy (TOF-SIMS) [140], Rutherford backscattering [167][168][169][170][171], high resolution electron energy loss spectroscopy (HREELS) [138], reflection absorption infrared spectroscopy (RAIRS) [172][173][174][175], direct recoil spectroscopy (DRS) [176], and scanning tunneling microscopy [177][178][179][180][181], to name only a few. In addition, an increasing number of theoretical studies and simulations have been conducted [101,[182][183][184][185][186][187][188][189][190].…”
Section: Molecular Insights Into Il/gas and Il/support Interfacesmentioning
confidence: 99%
“…Many established UHV-based surface science techniques have successfully contributed to an increasingly detailed understanding not only of the IL/ vacuum interface, but also of IL bulk properties. The applied methods include X-ray photoelectron spectroscopy (XPS) [106,107,, UV photoelectron spectroscopy [138,139,165,166], inverse photoelectron spectroscopy (IPES) [165,166], X-ray absorption spectroscopy (NEXAFS) [165], soft X-ray emission spectroscopy (SXES) [166], low energy ion scattering (LEIS) [141], metastable ion spectroscopy (MIES) [138,139], time-offlight secondary mass spectroscopy (TOF-SIMS) [140], Rutherford backscattering [167][168][169][170][171], high resolution electron energy loss spectroscopy (HREELS) [138], reflection absorption infrared spectroscopy (RAIRS) [172][173][174][175], direct recoil spectroscopy (DRS) [176], and scanning tunneling microscopy [177][178][179][180][181], to name only a few. In addition, an increasing number of theoretical studies and simulations have been conducted [101,[182][183][184][185][186][187][188][189][190].…”
Section: Molecular Insights Into Il/gas and Il/support Interfacesmentioning
confidence: 99%
“…Focussing on applications of ILs as solvent in electrochemistry, the potential dependent interaction of bulk ILs with a single crystal metal surface was investigated combining in situ scanning tunneling microscopy (STM) and cyclic voltammetry (CV). [28][29][30][31][32] In that work it was possible to gain insight into the structure formation on a molecular scale, combining high resolution STM imaging and XPS, which in combination with density functional calculations allowed us 3 to derive detailed information on the nature and order of magnitude of substrate -adsorbate interactions and the interactions between adjacent adsorbed IL species (adsorbateadsorbate interactions). Due to their extremely low vapour pressure, even thicker IL films can be investigated this way.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its high decomposition temperature, very low vapor pressure, and a large stability window ranging from −2.5 to 3.0 V versus Ag/AgCl (about 0–5 V vs. Li/Li + ), [BMP][TFSI] is a very promising candidate for LIBs. Special interest was placed on the interactions at the substrate|IL interface under UHV conditions by using several model substrates, for example, single‐crystalline metal surfaces, oxide surfaces, and highly oriented pyrolytic graphite . The above studies, which were conducted in the absence of an applied potential and which focused on the structure formation and the decomposition of the ionic liquid, clearly demonstrated that the chemical interaction with the substrate surface and/or with the added lithium is sufficient to cause decomposition of the IL.…”
Section: Introductionmentioning
confidence: 99%